2015
DOI: 10.1155/2015/754814
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spirituality on Cool Down Reactions, Work Engagement, and Life Satisfaction in Anthroposophic Health Care Professionals

Abstract: This study aimed to analyse whether spirituality is a resource for health care professionals to deal with increasing stress and work burden, specifically to analyse associations between “cool down reactions” (which describe an emotional distancing towards patients and/or reduced engagement as a strategy to protect their own functionality), work burden, and life satisfaction. We specifically focussed on anthroposophic health care professionals because of their unique approach to distinct aspects of spirituality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Spirituality and religiousness increased life satisfaction. This agrees with similar studies that report a significant and moderate relationship between life satisfaction and spirituality (Büssing et al, 2015). In the case of life satisfaction and religiousness, our results show a significant moderate relationship which is in line with similar…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Spirituality and religiousness increased life satisfaction. This agrees with similar studies that report a significant and moderate relationship between life satisfaction and spirituality (Büssing et al, 2015). In the case of life satisfaction and religiousness, our results show a significant moderate relationship which is in line with similar…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, studies in younger populations such as industrial employees in Indonesia, found that Islamic religiosity has a significantly positive impact on job satisfaction in small and medium-sized companies in the embroidery industry (Amaliah et al, 2015). Similarly, in a study carried out with infertile women from Iran (Etemadifar et al, 2016), in a population of athletes from the national team of the same country (Mirzaaghazadeh et al, 2016), and in professionals from the anthroposophic health field in Switzerland (Büssing et al, 2015), the same effect was demonstrated.…”
Section: Introductionmentioning
confidence: 80%
“…Na categoria 5 -Sistemas de saúde, os estudos pontuam os impactos das PICS na vida dos profissionais de saúde e, consequentemente, na assistência prestada às mulheres. Os profissionais de saúde com atuação antroposófica, quando comparados aos que atuam na medicina convencional, aparentam ter estratégias de regulação emocional que colaboram diante das condições estressoras de trabalho, que são associadas a Síndrome de Burnout, e aumentando a sua qualidade de vida (Büssing et al, 2015).…”
Section: Metodologiaunclassified
“…The approach is individualized and encompasses spiritual aspects. 10,12 ICC, particularly in AM, is a patient-centered approach. 8,13 Patient-centered care is a widely recognized central goal in health care and evidence-based medicine (EBM), 13,14 integrating clinical expertise and patient values along with best external evidence.…”
Section: Introductionmentioning
confidence: 99%